Tumor microenvironment in mycosis fungoides and Sézary syndrome. Issue 1 (January 2016) - Gonzalez, Belen Rubio; Zain, Jasmine; Rosen, Steven T.; Querfeld, Christiane
Abstract : Purpose of review: Mycosis fungoides and Sézary syndrome arise from malignant T cells that reside in skin, and subsequently are capable of circulating between skin, lymph nodes, and blood. The pathophysiologic mechanisms that cause and result in different behaviors of the skin-homing-malignant T cells in different stages of cutaneous T-cell lymphoma (CTCL) are still unknown. It is hypothesized that the skin microenvironment which is composed by various immune cell subsets as well as their spatial distribution and T-cell interaction through different chemokines and cytokines have an important role in the development and pathogenesis of CTCL and will be addressed in this chapter. Recent findings: Recent studies have discovered that malignant T cells in Sézary syndrome are of the central memory T-cell subset, whereas those in mycosis fungoides are nonrecirculating skin-resident effector memory T cells, and have shown a protumorigenic role of mast cells and macrophages in CTCL. In addition, it has been observed that malignant T cells may exhibit features of one of these three distinct phenotypes (forkhead box P3 + regulatory T-cell phenotype, Th2 phenotype, and Th17 phenotype) and are functionally exhausted through an increased expression of certain coinhibitory molecules, such as programmed death-1. Summary: All these new findings could assist in the development of novel targeted therapies for CTCL.